Laparoscopic Adrenalectomy for Adrenal Tumors. (14th July 2014) - Chuan-yu, Sun; Yat-faat, Ho; Wei-hong, Ding; Yuan-cheng, Gou; Qing-feng, Hu; Ke, Xu; Bin, Gu; Guo-wei, Xia
Abstract : Objective . To evaluate the indication and the clinical value of laparoscopic adrenalectomy of different types of adrenal tumor. Methods . From 2009 to 2014, a total of 110 patients were diagnosed with adrenal benign tumor by CT scan and we performed laparoscopic adrenalectomy. The laparoscopic approach has been the procedure of choice for surgery of benign adrenal tumors, and the upper limit of tumor size was thought to be 6 cm. Results . 109 of 110 cases were successful; only one was converted to open surgery due to bleeding. The average operating time and intraoperative blood loss of pheochromocytoma were significantly more than the benign tumors (P < 0.05 ). After 3 months of follow-up, the preoperative symptoms were relieved and there was no recurrence. Conclusions . Laparoscopic adrenalectomy has the advantages of minimal invasion, less blood loss, fewer complications, quicker recovery, and shorter hospital stay. The full preparation before operation can decrease the average operating time and intraoperative blood loss of pheochromocytomas. Laparoscopic adrenalectomy should be considered as the first choice treatment for the resection of adrenal benign tumor.